The relationship of factor that influencing the financial leverage : Manufacturing industries / Farah Nur Filza Baharudin - Baharudin, Farah Nur Filza (2017)
A poor management from the manufacturer may translate into the risky on the issuing debt of the firm. According to Goel, Chadha, & Sharma (2015), which insights on the interrelation between operation management and financial management and their impact on the firm's performance of the leverage. The company can increase their external financing to fund their future project if they have low business risk requirement. The decision for many companies to source for external debt relies on the capacity of the company. Credit default has been an arising issues tangling in the companies. Singh, Sharma, & Mathur (2012) stated that the small business firm will face difficulties in demonstrating their capacity not only to repay a loan but also to provide a collateral. This study aims to examine how selected factors influenced the financial leverage in manufacturing industry. This study enrolled the panel data which include the period of study from year 2012 to 2016 which comprises of 10 firms listed on the Bursa Malaysia. The dependent variables involve in this study is the financial leverage and considering the debt to capital ratio as the leverage variables. The profitability, tangibility, non-debt tax shield and liquidity are used to study the relationship influencing the dependent variables in the manufacturing industry which is evidence in Malaysia. This study is conducted by applying Pooled OLS regression though E-views. The findings from this paper show that the tangibility, non-debt tax shield and liquidity variables have a negative relationship on the financial leverage. However, the profitability shows a positive relationship on the financial leverage.